Effect of extraction temperature and time on the extraction of phenolic compounds and antioxidant capacity of Phaleria macrocarpa fruit - Lim, Yee Peng; Sook, Fun Pang; M. M., Yusoff; Jolius, Gimbun (Readers Insight Publisher, 2018)
Phaleria macrocarpa (ver. name:‘mahkota dewa’) is a plant which has many medically useful antioxidant activities (Anggraini & Lewandowsky, 2015). The polyphenols responsible for this antioxidant activity has to be extracted before it can be routinely used (Shwter et al., 2016). This study investigates the extraction of polyphenols from P. macrocarpa fruits and its antioxidant activity (DPPH-RSA) under influence of extraction time and temperature. By employing maceration technique, the P. macrocarpa fruits extract showed the maximum total phenolic content (TPC), total flavonoid content (TFC) and DPPH-RSA with value of 69.5 mg QE/g DW, 183.2 mg GA/g DW and 171. 8 mg BHA/g DW, respectively at optimum extraction conditions of 60 min and 80 ºC (Fig. 1). Excellent and positive Pearson correlation coefficient with R 2> 0.91 between the TPC, TFC and antioxidant activities was observed.